The impact of 27-hydroxycholesterol on endometrial cancer proliferation. Issue 4 (April 2018) - Gibson, Douglas A; Collins, Frances; Cousins, Fiona L; Esnal Zufiaurre, Arantza; Saunders, Philippa T K
Abstract : Endometrial cancer (EC) is the most common gynaecological malignancy. Obesity is a major risk factor for EC and is associated with elevated cholesterol. 27-hydroxycholesterol (27HC) is a cholesterol metabolite that functions as an endogenous agonist for Liver X receptor (LXR) and a selective oestrogen receptor modulator (SERM). Exposure to oestrogenic ligands increases risk of developing EC; however, the impact of 27HC on EC is unknown. Samples of stage 1 EC ( n  = 126) were collected from postmenopausal women undergoing hysterectomy. Expression of LXRs ( NR1H3, LXRα; NR1H2, LXRβ) and enzymes required for the synthesis ( CYP27A1 ) or breakdown ( CYP7B1 ) of 27HC were detected in all grades of EC. Cell lines originating from well-, moderate- and poorly-differentiated ECs (Ishikawa, RL95, MFE 280 respectively) were used to assess the impact of 27HC or the LXR agonist GW3965 on proliferation or expression of a luciferase reporter gene under the control of LXR- or ER-dependent promoters (LXRE, ERE). Incubation with 27HC or GW3965 increased transcription via LXRE in Ishikawa, RL95 and MFE 280 cells ( P  < 0.01). 27HC selectively activated ER-dependent transcription ( P  < 0.001) in Ishikawa cells and promoted proliferation of both Ishikawa and RL95 cells ( P  < 0.001). In MFE 280 cells, 27HC did not alter proliferation but selective targeting of LXR with GW3965 significantly reduced cell proliferation ( P  < 0.0001). These novel results suggest that 27HC can contribute to risk of EC by promoting proliferation of endometrial cancer epithelial cells and highlight LXR as a potential therapeutic target in the treatment of advanced disease.